Takhrij and Syarah Hadith of Agrotechnology Study of the Benefits of Dates - Fahrido Dasril; Wahyudin Darmalaksana; Dadang Darmawan; Esty Puri Utami (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith regarding the efficacy of dates. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The results and discussion of this study are the efficacy of dates which are recommended to eat them every day in moderation. The efficacy of dates when consuming them has been known from several studies. The conclusion of this research is takhrij and syarah hadith of the Prophet. about dates with agrotechnology analysis informs that the content of dates is beneficial for the fitness of the human body.